2023
DOI: 10.1177/15593258231169387
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Membranes of Chitosan/Aloe Vera Gel Fabrication With Enhanced Swelling and Antimicrobial Properties for Biomedical Applications

Abstract: Since ancient times, medicinal plants have been used as traditional medicine to treat a variety of ailments. Aloe vera (AV) gel’s therapeutic potential is one of the most effective approach in the fabrication of functional materials. The current study aimed to prepare the AV and chitosan (CS) membranes using various cross-linkers that were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform-infrared (FT-IR) spectroscopy, thermal gravimetric analysis (TGA), and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Meanwhile, AVG contains polysaccharides and other lubricants ( Mohammadi et al, 2021 ). The CTS/AVG solution had the maximum viscosity of 24.60 ± 0.20 cP, possibly due to its capacity to build a network of cross-linked polymer chains that impede liquid movement ( Iqbal et al, 2023 ). OPEO contains terpenoids and other chemicals with various physiological effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, AVG contains polysaccharides and other lubricants ( Mohammadi et al, 2021 ). The CTS/AVG solution had the maximum viscosity of 24.60 ± 0.20 cP, possibly due to its capacity to build a network of cross-linked polymer chains that impede liquid movement ( Iqbal et al, 2023 ). OPEO contains terpenoids and other chemicals with various physiological effects.…”
Section: Resultsmentioning
confidence: 99%
“…It is clearly shown that CTS/AVG only shows significant antimicrobial activity against Pseudomonas aeruginosa with an inhibition zone of 10.5 ± 1.3 mm. There was no substantial bactericidal potential of aloe vera in the chitosan matrix, which may be because the bioactive components of aloe vera gel were trapped by the high concentration of chitosan ( Iqbal et al, 2023 ). Incorporation of OPEO in CTS/AVG coating solutions increased the susceptibility of tested bacteria, thus increasing the zone of inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…A good dressing material with antibacterial characteristics is necessary in such a situation. 1 - 6 Dressings are crucial in preventing infection and boosting growth factors for faster healing. 7 , 8 Traditional wound dressings are primarily dry and challenging to apply, and they cannot heal patients.…”
Section: Introductionmentioning
confidence: 99%